Designing a 3D printable polypropylene-based material from after use recycled disposable masks. (August 2022) - Battegazzore, D.; Cravero, F.; Bernagozzi, G.; Frache, A.
Abstract: Different percentages of talc were added to polypropylene deriving from pristine surgical masks in a small scale extrusion equipment to confer specific rheological and thermal properties to the resulting materials. This is not a fully satisfactory solution, thus the quantity of masks has been partially replaced by a first-use polypropylene copolymer. Two selected formulations with 35 and 50 wt% of material deriving from pristine masks and 30 wt% of talc have been identified as suitable for the 3D printing process. Finally, the formulations were scaled up with a lab twin-screw extruder and by recycling sanitized after use masks to be as close as possible to field recycling conditions. The extruded pellets were processed to produce printing filament and finally validated as extrusion material for 3D printing. 3D printed tensile specimens were characterized for the mechanical properties and observed for their microstructure even comparing them with a commercial 3D printable material. For the first time is verified that a 3D printable extrusion material recycled from the disposable face masks can be obtained and shows comparable stiffness and strength to a commercial one. Graphical Abstract: ga1